Into the savage country [large type] - Burke, Shannon (Center Point Large Print, 2015)
"Young William Wyeth leaves St. Louis for a fur-trapping expedition in 1826 and finds himself unwittingly at the center of a deadly boundary dispute among Native American tribes, the British government, and American trapping brigades"--